Komunikasi Pendidikan (Urgensi Komunikasi Efektif dalam Proses Pembelajaran) - Ujang Mahadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effectiveness of educational communication in the learning process. This study uses a quantitative approach, with explanatory research methods. The results of the study show that communication is an important part, a basic need and a medium for interacting with others to convey feelings, opinions, thoughts, information, advice and share experiences with others. Effective communication is also an important part of educational communication to convey educational messages in the learning process. Educational communication is said to be effective if the subject matter delivered by educators can be well received and understood and generates positive feedback by students. The conclusion of this research is that educators need to learn